Cardiac regeneration and remodelling of the cardiomyocyte cytoarchitecture. (6th December 2019) - Ali, Hashim; Braga, Luca; Giacca, Mauro
Abstract : Adult mammals are unable to regenerate their hearts after cardiac injury, largely due to the incapacity of cardiomyocytes (CMs) to undergo cell division. However, mammalian embryonic and fetal CMs, similar to CMs from fish and amphibians during their entire life, exhibit robust replicative activity, which stops abruptly after birth and never significantly resumes. Converging evidence indicates that formation of the highly ordered and stable cytoarchitecture of mammalian mature CMs is coupled with loss of their proliferative potential. Here, we review the available information on the role of the cardiac cytoskeleton and sarcomere in the regulation of CM proliferation. The actin cytoskeleton, the intercalated disc, the microtubular network and the dystrophin–glycoprotein complex each sense mechanical cues from the surrounding environment. Furthermore, they participate in the regulation of CM proliferation by impinging on the yes‐associated protein/transcriptional co‐activator with PDZ‐binding motif, β‐catenin and myocardin‐related transcription factor transcriptional co‐activators. Mastering the molecular mechanisms regulating CM proliferation would permit the development of innovative strategies to stimulate cardiac regeneration in adult individuals, a hitherto unachieved yet fundamental therapeutic goal. Abstract : The regenerative potential of the heart drops immediately after birth as cardiomyocytes exit the cell cycle while they progressively expand and structure their sarcomeres. Converging evidence now indicates that the actin cytoskeleton, the intercalated disc, the microtubular network and the dystrophin–glycoprotein complex each sense mechanical cues from the surrounding environment and participate in the regulation of cardiomyocyte proliferation.